Heat distribution under microwave heating treatment - Siti Zulaika Abdul Nyzam; Rosemizi Abd Rahim (Institute of Advanced Engineering and Science, 2019)
This paper presents the process of microwave heating treatment to kill the rice weevil to improve the quality and quantity of rice for industrial storage purpose. Since many years ago, heat uniformity has been a major drawback of microwave heating application. The heat distribution in rice after undergoing four treatments with a microwave frequency of 2.4 GHz at the different power level of 540 and 900W with different time treatment of 50 and 80 seconds are shown in this paper. The samples are placed inside a square container, 8.5 cm x 8.5 cm x 2 cm. Each sample contains 15 adults of rice weevil of Sitophilus Oryzae placed randomly in the container and the mortality of the rice weevil for adult stages from each treatment are observed and interpreted in Analysis of Variance (ANOVA) technique.